Principles of mental hygiene - Gaerlan, Josefina E.; Limpingco, Delia A. ; Tria, Geraldine E. (Quezon city, 2008)
This edition is streamlined into the holistic point of view of Mental Health and current research studies. Guide questions have been prepared to help students master the contents of textual material and to prepare for self-assessments. Practitioners/professors can use these questions for preparing examinations...
Keywords: Mental health